2015
DOI: 10.1007/s00213-015-3869-2
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of nicotine effects on selective attention by DRD2 and CHRNA4 gene polymorphisms

Abstract: The effects of nicotine on distractor interference are modulated synergistically by cholinergic and dopaminergic genetic variations. Hence, both genes may contribute to the often reported individual variability in cognitive and neural effects of nicotine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
7
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 45 publications
4
7
0
1
Order By: Relevance
“…The cardiovascular effects of nicotine are in line with many prior findings with an increase in heart rate and/or blood pressure under nicotine [10,20,46,47]. …”
Section: Discussionsupporting
confidence: 71%
“…The cardiovascular effects of nicotine are in line with many prior findings with an increase in heart rate and/or blood pressure under nicotine [10,20,46,47]. …”
Section: Discussionsupporting
confidence: 71%
“…The genetic polymorphisms investigated here may impact such dynamic interplay and modulate the effects of systemically administered nicotine. We have recently shown that DRD2 T-/CHRNA4 C+ subjects are also more responsive to the effects of nicotine on distractor interference, which corroborates the present findings [47]. A recent study further underlines the interactions between cholinergic and dopaminergic polymorphisms in showing epistatic effects of CHRNA5 and DRD2 on working memory and prefrontal cortex activity [48].…”
Section: Discussionsupporting
confidence: 89%
“…A recent study further underlines the interactions between cholinergic and dopaminergic polymorphisms in showing epistatic effects of CHRNA5 and DRD2 on working memory and prefrontal cortex activity [48]. Taken together, it can be concluded that the attentional effects of nicotine reported here and in our prior study [47] are primarily seen in subjects with high dopaminergic activity (i.e. DRD2 T-) and a presumably higher rate of nicotinic receptors in high affinity state (i.e.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…, gene envolvido na modulação da locomoção, reforço, memória e aprendizagem e têm sido associado à diversas patologias psiquiátricas na literatura como, por exemplo, esquizofrenia (Lencz et al, 2015;Yao et al, 2015), depressão (Savitz et al, 2013;Pearson-Fuhrhop et al, 2014); jogo patológico (Hillemacher et al, 2015) e dependência de álcool (Delis et al, 2015), nicotina (Ahrens et al, 2015;Ma et al, 2015), opiáceos (Nelson et al, 2014;Levran et al, 2015), maconha (Colizzi et al, 2015;DiNieri et al, 2015) e cocaína (Noble et al, 1993). A relação entre o gene DRD2 e o abuso/dependência de cocaína têm sido investigada em diversos estudos em animais (Lee et al, 2006;Bertran-Gonzalez et al, 2008;Lawhorn et al, 2013) e humanos.…”
Section: Drd2 (Dopamine Receptor D2)unclassified